The potential of the special purpose forest area of Lambung Mangkurat University as a biology learning resource - Hendra Hendra; Mochamad Arief Soendjoto (HAFECS PRESS, 2024)
Special Purpose Forest Area of Lambung Mangkurat University (KHDTK ULM) is a forest area whose management is handed over by the Ministry of Environment and Forestry to Lambung Mangkurat University for education and training purposes. As an educational institution, ULM should already have data regarding the diversity and richness of living species in the forest area. This diversity and wealth must of course be utilized sustainably. This research aims to analyze the potential of KHDTK ULM and its use as a biology learning resource. The method used in research is literature study. The literature in this case is various publications published in the last five years and can be accessed on Google Scholar as well as the Sinta ranking. Quite a lot of plants and animals have been used as research objects, but many still need to be explored in more depth. Research results should not just be turned into articles to be published in scientific journals, but also developed further into learning materials. Conditions like this also show the potential of forest areas as a source of learning biology, not only to increase knowledge but also to train critical thinking skills. Abstrak. Kawasan Hutan Dengan Tujuan Khusus Universitas Lambung Mangkurat (KHDTK ULM) adalah kawasan hutan yang pengelolaannya diserahkan oleh Kementerian Lingkungan Hidup dan Kehutanan kepada Universitas Lambung Mangkurat untuk tujuan pendidikan dan pelatihan. Sebagai lembaga pendidikan, sudah selayaknya ULM memiliki data terkait dengan keragaman dan kekayaan spesies makhluk hidup di kawasan hutan tersebut. Keragaman dan kekayaan itu harus dimanfaatkan berkelanjutan. Penelitian ini bertujuan untuk menganalisis potensi KHDTK ULM dan pemanfaatannya sebagai sumber belajar biologi. Metode yang digunakan dalam penelitian adalah studi pustaka. Pustaka dalam hal ini adalah berbagai publikasi yang terbit dalam kurun lima tahun terakhir dan dapat diakses pada Google Scholar serta pemeringkatan Sinta. Cukup banyak tumbuhan dan hewan yang telah dijadikan obyek penelitian tetapi banyak yang masih perlu diungkap lebih dalam. Hasil penelitian pun seharusnya tidak sekedar dijadikan artikel untuk dipublikasi pada jurnal ilmiah, tetapi juga dikembangkan lebih jauh menjadi bahan pembelajaran. Kondisi seperti ini sekaligus menunjukkan potensi kawasan hutan sebagai sumber belajar biologi, tidak sekedar untuk meningkatkan pengetahuan tetapi juga untuk melatihkan keterampilan berpikir kritis.